Sebuah Urgensi pendanaan Program Kreative mahasiswa(PKM) dalam Triple helix guna kemandirian industri pertahanan - Ramadhan, Muhammad Taufiq; I Nengah Putra; Timbul Siahaan; Rudy AG Gultom; Vicky A Nugroho (CV. AFDIFAL MAJU BERKAH, 2023)
The urgency of funding student creativity programs within the Triple Helix framework to encourage the independence of the defense industry is a step forward in making economic progress, especially the defense industry. The SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method is used as a research framework to evaluate the internal and external factors that influence the success of the program. This research reveals that funding for student creativity programs has a significant urgency in strengthening the defense industry. Through collaboration between students, industry and the government, this program is able to generate innovation, research and development of new technologies that can increase the competitiveness of the defense industry. The SWOT analysis shows that the strengths of the student creativity program in Triple Helix include access to fresh and innovative student intellectual resources, the ability to combine academic knowledge with the needs of the defense industry, and the encouragement of collaboration and knowledge exchange between all parties involved. Weaknesses identified include a lack of adequate funding, challenges in integrating student activities into a complex industrial environment, and a lack of understanding of the long-term benefits of the program. However, the SWOT analysis also identified significant opportunities, such as the increasing need for innovation and new technologies in the defense industry, government support for collaborative programs involving students, and the potential to develop long-term partnerships between the defense industry and universities. The threats faced include intense global competition, the need for constant updating of defense technology, and the potential for gaps between academic knowledge and industry needs if there is not adequate collaboration. In order to realize the independence of the defense industry, this research recommends adequate funding for student creativity programs, provision of supporting infrastructure, increased collaboration between universities, industry and government, as well as the development of a long-term strategy to ensure the sustainability of this program.